Comparative assessment of efficacy of topical propranolol in superficial hemangioma. - Bonifazi, E.; Milano, A. (European Journal of Pediatric Dermatology, 2013)
When in 2008 we proposed the use of topical propranolol for superficial hemangioma - H - (1), we decided to verify its real effectiveness. Initially, we compared the effectiveness in two series of H with similar clinical features, proposing random topical therapy only in a series and not in the other (2). However, the number of similar H was not enough to give a statistically sound answer. So we opted for treating topically for the first month only a half of H (2), but we gave up this method when we realized that the half treated earlier responded much better to treatment even after 6 months from the beginning of overall treatment of hemangioma (3). Currently, in case of multiple H we continue to monitor the effectiveness treating only that one needing more a therapy.